2002
DOI: 10.1002/j.2161-1912.2002.tb00521.x
|View full text |Cite
|
Sign up to set email alerts
|

Race, Class, and Gender: A Constellation of Positionalities With Implications for Counseling

Abstract: Race, class, and gender are social, political, economic, and cultural constructs that describe the posifionalities of people. How these constructs are defined depends on the status occupied by individuals and the individual, institutional, and societal status of the individuals who have the power to construct hierarchies. The authors examine the intersection of race, class, and gender and the dimensions of oppression and discrimination in counseling. Historical and contemporary dimensions of racism, misogyny, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 32 publications
0
47
1
3
Order By: Relevance
“…M. Jordan, 1991J. M. Jordan, , 1997, resisting racism (Comas-Diaz & Greene, 1994;Fischer & Shaw, 1999;Landrine, 1995;Tinsley-Jones, 2003), and, more recently, integrating multiple identities (Constantine, 2002;Croteau et al, 2002;Harley et al, 2002;Moradi & Subich, 2003). When working therapeutically with African American women, it is essential for therapists to assist their clients in recognizing the sociocultural genesis and impact of racism, sexism, classism, and homophobia (Semmler & Williams, 2000).…”
Section: Strategies For Integrating Multiple Cultural Identitiesmentioning
confidence: 95%
See 1 more Smart Citation
“…M. Jordan, 1991J. M. Jordan, , 1997, resisting racism (Comas-Diaz & Greene, 1994;Fischer & Shaw, 1999;Landrine, 1995;Tinsley-Jones, 2003), and, more recently, integrating multiple identities (Constantine, 2002;Croteau et al, 2002;Harley et al, 2002;Moradi & Subich, 2003). When working therapeutically with African American women, it is essential for therapists to assist their clients in recognizing the sociocultural genesis and impact of racism, sexism, classism, and homophobia (Semmler & Williams, 2000).…”
Section: Strategies For Integrating Multiple Cultural Identitiesmentioning
confidence: 95%
“…Recent counseling literature has begun to address this problem (Constantine, 2002;Croteau et al, 2002;Harley et al, 2002), yet further attention to therapeutic limitations of compartmentalizing cultural variables clearly is needed, as are therapeutic strategies that support clients who wish to claim multiple cultural identities.…”
mentioning
confidence: 98%
“…These social dynamics may help to explain scores reflecting greater bias in these two domains. Robinson (1999), followed by Harley, Jolivette, McCormick, and Tice (2002), observed that counselors occupy a privileged position not only by virtue of their profession but also by the value accorded to them by membership in advantaged cultural groups (e.g., based on race, social class). As such, they are called upon to recognize and address their encapsulated perspectives so that they can provide bias-free counseling environments.…”
Section: Social Classmentioning
confidence: 98%
“…Herhaaldelijk wijzen auteurs er op dat de onderdrukkende relaties waarin cliënten verwikkeld zijn geweest zich niet mogen herhalen in wat wel de micropolitieke situatie van de hulpverlening wordt genoemd (Burman, 2004;Harley et al, 2002). Om dat te vermijden is zelfreflectie nodig van counselors Soms bieden ervaringen die hulpverleners (m/v) zelf met minorisering hebben een kans om contact te leggen met geminoriseerde cliënten of in ieder geval de drempel te verlagen.…”
Section: W E R K R E L a T I Eunclassified